2024
DOI: 10.1111/pace.14971
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of pulsed‐field ablation versus cryoablation for atrial fibrillation

Hehua Zhang,
Hua Zhang,
Heng Lu
et al.

Abstract: PurposeThe available data on the treatment strategy of pulsed field ablation (PFA) for patients with atrial fibrillation (AF) is limited. This study aims to provide a comparative analysis of the efficacy, safety, and procedural efficiency between PFA and cryoballoon ablation (CBA) for AF.MethodsWe conducted a comprehensive search of the EMBASE, PubMed, Cochrane Library, and ClinicalTrials.gov databases to identify trials comparing PFA with CBA for AF from their inception until December 2023. The odds ratio (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
3
0
0
Order By: Relevance
“…From the analysis of six comparative studies involving a total of 1,012 patients, the main conclusion of Aldaas et al was that pulse-field ablation is associated with shorter procedural times and longer fluoroscopy times, but there is no difference in periprocedural complications or rates of recurrent atrial fibrillation compared with thermal ablation. These results of Aldaas et al are consistent with those recently published by Zhang et al [ 18 ], whose meta-analysis based on 15 studies compared pulse-field ablation and cryoablation for safety and procedural efficiency; the main safety endpoints included periprocedural complications, procedure time, and fluoroscopy time. The conclusions of Zhang et al [ 18 ] are in favor of pulse-field ablation, as it was shown to be a safer, time-saving, and tissue-specific procedure compared to cryoablation, with comparable success rates; this has the potential to improve procedural efficiency and optimize resource utilization in clinical practice.…”
Section: Reviewsupporting
confidence: 87%
See 2 more Smart Citations
“…From the analysis of six comparative studies involving a total of 1,012 patients, the main conclusion of Aldaas et al was that pulse-field ablation is associated with shorter procedural times and longer fluoroscopy times, but there is no difference in periprocedural complications or rates of recurrent atrial fibrillation compared with thermal ablation. These results of Aldaas et al are consistent with those recently published by Zhang et al [ 18 ], whose meta-analysis based on 15 studies compared pulse-field ablation and cryoablation for safety and procedural efficiency; the main safety endpoints included periprocedural complications, procedure time, and fluoroscopy time. The conclusions of Zhang et al [ 18 ] are in favor of pulse-field ablation, as it was shown to be a safer, time-saving, and tissue-specific procedure compared to cryoablation, with comparable success rates; this has the potential to improve procedural efficiency and optimize resource utilization in clinical practice.…”
Section: Reviewsupporting
confidence: 87%
“…These results of Aldaas et al are consistent with those recently published by Zhang et al [ 18 ], whose meta-analysis based on 15 studies compared pulse-field ablation and cryoablation for safety and procedural efficiency; the main safety endpoints included periprocedural complications, procedure time, and fluoroscopy time. The conclusions of Zhang et al [ 18 ] are in favor of pulse-field ablation, as it was shown to be a safer, time-saving, and tissue-specific procedure compared to cryoablation, with comparable success rates; this has the potential to improve procedural efficiency and optimize resource utilization in clinical practice.…”
Section: Reviewsupporting
confidence: 87%
See 1 more Smart Citation